Intrinsic factors associated with medial tibial stress syndrome in athletes: A large case-control study - Winters, M; Veldt, H; Bakker, EW; Moen, MH (South African Journal of Sports Medicine, 2013)
Background. Medial tibial stress syndrome (MTSS) is the most common lower-leg injury in athletes, and is thought to be caused by bony overload. To prevent MTSS, both pathophysiological and aetiological factors specific to MTSS need to be identified. The intrinsic risk factors that contribute to the development of MTSS are still uncertain. Objective. To determine the intrinsic risk factors of MTSS by sampling a large population of athletic MTSS patients and controls. Methods. Athletes with MTSS and control subjects were medically examined in terms of range of motion of the leg joints (hip abduction, adduction, internal and external range of motion; ankle plantar and dorsal flexion; hallux extension and flexion; subtalar inversion and eversion), measures of over-pronation and maximal calf girth. Results. Ninety-seven subjects agreed to participate in the study: 48 MTSS patients and 49 active controls. The following variables were considered: gender, age, body mass index (BMI), hip abduction, hip adduction, internal and external hip range of rotation, ankle plantar and dorsal flexion, hallux flexion and extension, subtalar inversion and eversion, maximal calf girth, standing foot angle and navicular drop test. In multivariate logistic regression analysis, hip abduction (odds ratio (OR) 0.82; 95% confidence interval (CI) 0.72 - 0.94), ankle plantar flexion (OR 0.73; 95% CI 0.61 - 0.87) and subtalar inversion (OR 1.24; 95% CI 1.10 - 1.41) were significantly associated with MTSS. The Nagelkerke R2 for this model was 0.76, indicating that 76% of the variance in the presence of MTSS could be explained by these variables. Conclusion. Decreased hip abduction, decreased ankle plantar flexion and an increased subtalar inversion could be considered risk factors for MTSS.